NUMERICAL STUDIES ON THE BENDING PERFORMANCE OF COLD-FORMED COMPOSITE CONCRETE-FILLED STEEL BEAMS (CFSB) (Al-Farooq Journal of Sciences, 2026)
Cold-formed steel (CFS) composite sections have recently been introduced with other materials, such as concrete, and fastened with bolts and screws to avoid the buckling problem of the cold-formed steel sections. The flexural analysis of CFS concrete beams is more complex in terms of design and failure mode. Therefore, this paper provides a brief review of numerous studies of CFS sections, with and without concrete, under bending loads. In particular, the buckling failure modes of CFS are critically examined. Important considerations such as defining material properties and interactions during numerical simulations are also discussed. The review presented here highlights significant potential for understanding how nonlinearity in the concrete material, the interaction of CFS with concrete, and connection types affect the simulation accuracy in predicting the bending behavior of composite beams. Furthermore, connection types, nonlinear simulation methods and strategies, and results related to the bending behavior of CFS concrete are reviewed. Future research directions were identified through concluding observations and recommendations to achieve higher accuracy in simulation results and a more effective design philosophy for the future to promote the use of CFS composite beams in the construction industry.
Keywords: Cold-formed steel sections, fastening connections, concrete, bending behavior, interactions, numerical simulation